Perfil do procedimento da ação cautelar coletiva antecedente - Caseiro Neto, Francisco da Silva (2019)
Before the threat of violation of the individual, public and colective right, there is no way to evade the aplication of the absolute right of action, upon the process and jurisdictional dictum of merit (substantial cautionary right) – true to the Liebman trinomial doctrine – in the face of the cautionary antecedent action, which presents itself as part of the main action and provided with its own liminal. In this constitutional and procedural scenario, the common procedure applicated to it is uncovered, modulated to the high criterion of the judge, under the light of the danger of delay, (Calamandrei’s unsuccessfulness, true conservation in oblique line to the main request) and the probability of success in the final solution of demand, developing itself, sometimes incorporated, sometimes independent of the main procedure